Trust No One? Security and International Trade - Jerónimo Carballo; Georg Schaur; Christian Volpe Martincus (Inter-American Development Bank (IDB), 2016)
Security concerns in a context of increasingly segmented supply chains have led to stricter border control measures, which may potentially negatively affect international trade. Customs around the world have therefore implemented security-motivated certification programs to facilitate licit trade. These programs offer trustworthy trading firms, i.e., Authorized Economic Operators (AEOs), several advantages in the administrative processing of their shipments including less frequent physical inspections and expedited customs clearance. In this study we focus on Mexico's AEO Program NEEC. In particular, we evaluate the impact of this program by primarily carrying out differences-in-differences estimations on highly disaggregated firm-level data that cover the entire universe of export and import transactions of the country over the period 2009-2014. Estimation results suggest that NEEC has been associated with less physical inspections and shorter clearance times and has thereby favored increased firms' exports. Effects seem to be stronger on the frequency of shipments and on consumer goods, industrial inputs, and capital goods.
hdl:11319/7684
Keywords: F10; F13; F14; 330; Security; Authorized Economic Operator; Trade; Mexico